Oil Mist Lubrication Control System using Programmable Logic Controller - Thongprasri, Pairote; Poolphaka, Paisak (Frontiers in Engineering Innovation Research, 2020)
This paper presents an oil mist lubrication control system using NX1P2 Programmable Logic Controller (PLC) instead of microcontroller. The PLC control program is designed according to the IEC61131-3 standard structure. The control system can be set and displayed the operation via a human machine interface model NB7W-TW01B. There are 7 sensors used in the control system, which are divided into 3 types; level sensor, temperature sensor, and pressure sensor. These sensors send the signals to PLC to control the status light, oil solenoid valve, oil heater, and air heater through the solid state relay and mechanical relay. The PLC control program uses the Auto-tuning function to calculate the appropriate values of Kp, Ki and Kd for the system. Program testing; the heater operates when the temperature reaches the set value, the air pump operates if the air pressure is between the set value, and the oil pump operates when the oil level is below the set lower value, it stops when the oil level is higher than the set top value. The results confirm the accuracy and reliability of the proposed control system. In addition, the system can alert via status light and store data or events. The oil mist lubrication control system using the PLC is used at PTTGC # 4, which is set up according to the Site Acceptance Test. The result, the system operates correctly and efficiently.